Stereoselective Gold(I)‐Catalyzed Vinylcyclopropanation via Generation of a Sulfur‐Substituted Vinyl Carbene Equivalent. (21st December 2020) - Yuan, Tengrui; Ryckaert, Bram; Van Hecke, Kristof; Hullaert, Jan; Winne, Johan M.
Abstract: A stereoselective gold(I)‐catalyzed vinylcyclopropanation of alkenes has been developed. A gold‐coordinated cationic vinyl carbene species, readily generated via a rearrangement of the ethylenedithioacetal of propargyl aldehyde, reacts with a wide range of alkenes to afford thio‐substituted vinylcyclopropanes. The gold‐catalyzed vinyl cyclopropanation proceeds under mild conditions at room temperature and is generally selective for the formation of cis ‐substituted cyclopropanes. The reaction allows the formal introduction of a "naked" vinyl carbene, by subsequent chemoselective hydrodesulfurisation of the ethylenedithio‐bridge. The synthetic utility of the new method is demonstrated by a short, racemic formal synthesis of the alkaloid cephalotaxin, hinging on a key vinyl cyclopropane‐cyclopentene rearrangement. Abstract : A cationic gold(I)‐coordinated vinylcarbene species can be generated from simple propargylaldehyde ethylenedithioacetal and engages a wide range of alkenes in a catalytic stereoselective cyclopropanation. This method was used as a key step to elaborate the polycyclic framework of cephalotaxus alkaloids.